Who Sets the Agenda in the Hybrid Media Sphere? - Rok Smrdelj (Annales, Series Historia et Sociologia)
Building on the hybrid media system model, our study examines mass media’s role in shaping the Slovenian Twitter (X) migration debate. The analysis revealed that mass media actors, both “older” and “newer”, predominantly with a right-wing orientation, were among the most influential users. The discourse analysis of the most retweeted tweets revealed the coexistence of security and humanitarian perceptions on migration, indicating that Twitter’s migration discourses did not significantly deviate from those prevalent in mass media. Our findings illustrate how mass media have effectively adapted to Twitter’s media logic, utilising it as a channel for content distribution.